A New Measure of Attributable Risk for Public Health Applications - Cox, Louis A. (Management Science, 1985)
A persistent conceptual problem in the theory of risk accounting and risk analysis methodology is that of allocating or attributing a risk among the joint causes or “factors” producing it. When multiple factors interact, the especially difficult problem of “risk externalities” arises. Drawing on related work in the mathematical theory of games that seeks solutions to similar philosophical and conceptual problems, this paper proposes a method for solving the risk attribution problem. The proposed solution is justified on the grounds that it is the unique risk attribution function satisfying three reasonable principles, or “axioms,” of risk accounting. A mathematical framework for formulating risk attribution problems, and several possible applications, are also discussed.